Web-Based System Integration in Digital Transformation of Bureaucracy and Company Management Using Agile Methods - Wiko Pratama; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2024)
Digital transformation has become a fundamental need in improving bureaucratic efficiency and company management. In this context, the implementation of web-based systems and Agile methods at PT Lion Mentari Airlines aims to speed up administration, reduce manual errors, and improve information accessibility. This study examines the integration of web-based systems in digital transformation using an Agile approach consisting of the Product Backlog, Sprint Planning, and Development stages. The developed system includes key features such as user management, attendance, leave application, and FAQ, which significantly improves operational efficiency and service quality. The results show that the application of Agile in the development of web-based systems has succeeded in reducing the potential for errors, speeding up administrative processes, and improving interaction between users and management. Thus, the integration of this system makes a great contribution to improving the company's efficiency and providing more effective solutions in managing administration and services to employees.